(untitled) (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2018)
INTRODUCTION: The lexical availability (DL) The lexical availability is a field of linguistic research that aims to collect, analyze and value, both quantitatively and qualitatively, the lexicon available in a speaking community. The aim of this study is to describe the availability of students enrolled in the first semester, the last and the teach-ers enrolled in the Phonoaudiology program of the University of Pamplona, Pamplona and Cúcuta, METHODS: in order to obtain information about their lexical availability more specifically about the Data of lexical variability, frequency by use and categories of words organized by center of interest. RESULTS: A written availability sur-vey was applied, and the results were then found in the DispoGen software to determine lexical availability and cohesion indexes, as well as the totality of words and words. ANALYSIS AND DISCUSSION: The most striking result is that the years of experience are a factor that, as expected, influence the number of responses provided. CONCLUSIONS: There is a growing lexicon available to students as their years of study increase. However, it has been observed that both teachers and students have less lexical availability in areas such as orofacial motor and voice.